2020
DOI: 10.1515/gcla-2020-0005
|View full text |Cite
|
Sign up to set email alerts
|

Patterns ‘We’ Think By? Critical Cognitive Linguistics Between Language System and Language Use

Abstract: Taking the interrelationship of language and thought as starting point, Cognitive Linguistics considers language as providing central insights into cognitive structures and processes as well as into their experiential basis. In its role as a gateway for exploring and describing phenomena at the interface between the individual and society by means of public language use, Cognitive Linguistics thus ranges between the poles of trans-situational, overarching language structures and situated, specific language use… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 22 publications
0
1
0
Order By: Relevance
“…The easiest way in which this pervasiveness of subjectivity can be observed is at the lexical level: the choice of words definitely reflects social and personal perspectives, opinions, and stances (Lin et al, 2006 ). Other work has shown that more subtle ways of expressing perspectives in discourse can be found at the syntax-semantic interface (Horst, 2020 ; Te Brömmelstroet, 2020 ; Pinelli and Zanchi, 2021 ; Minnema et al, 2022 ). While most work in Computational Linguistics and Natural Language Processing still focuses on language phenomena on which humans agree to a large extent, there is a growing interest in modeling people's perspectivization of a shared event or language phenomenon by taking into account their own interests, agenda, and how that influences the way in which communication is perceived.…”
mentioning
confidence: 99%
“…The easiest way in which this pervasiveness of subjectivity can be observed is at the lexical level: the choice of words definitely reflects social and personal perspectives, opinions, and stances (Lin et al, 2006 ). Other work has shown that more subtle ways of expressing perspectives in discourse can be found at the syntax-semantic interface (Horst, 2020 ; Te Brömmelstroet, 2020 ; Pinelli and Zanchi, 2021 ; Minnema et al, 2022 ). While most work in Computational Linguistics and Natural Language Processing still focuses on language phenomena on which humans agree to a large extent, there is a growing interest in modeling people's perspectivization of a shared event or language phenomenon by taking into account their own interests, agenda, and how that influences the way in which communication is perceived.…”
mentioning
confidence: 99%